AN ANALYSIS ON CBT NATIONAL EXAMINATION EFFECT: STUDENTS’ COGNITIVE READINESS AND ANXIETY FACING ENGLISH TESTS - PIPIT MULIYAH (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
The purpose of this study was to know the influence of CBT and PBT national examination dealing with students’ cognitive readiness and anxiety facing English national examination in Cilacap regency, the influence of major in terms of students’ cognitive readiness and anxiety facing English national examination in Cilacap regency, and the interaction between national examination and major. This research was descriptive explorative and the method was ex-post facto. The population was all of natural and social science high school students in grade XII in Cilacap regency. The number of sample used was 352 students. The results showed that there was significant influence of national examination in terms of students’ cognitive readiness and anxiety facing national examination. However, CBT and PBT national examination did not influence the cognitive readiness facing national examination, CBT and PBT national examination influence in national examinations in terms of students’ anxiety facing national examination. The average score of the students’ anxiety facing CBT national exam was higher than that of the students’ anxiety facing PBT national examination. There was no effect caused by differences in majoring in terms of cognitive readiness and anxiety in facing English national examination; and there was no interaction between the different types of national examinations and majors.